Precipitation of nickel and cobalt sulphides using different reactor configurations - Swartbooi, Ashton Mark (Department of Chemical Engineering, 2014)
The nickel reduction process produces a stream containing unreacted dissolved nickel and cobalt. Removal of these metals to optimum levels is desired, however, the product should also be easy to handle and the process easy to incorporate into the current system. There are various precipitation agents that can be used to remove metals from solution, these being hydroxide, carbonates or sulphides. Sulphide precipitation has been gaining increased attention because of the advantages it holds above the other methods. These include: - attainment of high degree of metal removal over a broad pH range; - effective removal of metals such as As, eu and Hg even at low pH; - low retention time required in the reaction tank because of high reactivity; - feasibility of selective metal recovery There are various methods of introducing the sulphide into the system as well, with a soluble sulphide source most commonly used. The problem with this, and coupled to the high reactivity of the sulphide ion, is the creation of high local supersaturation. The supersaturation governs all precipitation and crystallisation processes in the way that it features in nucleation and growth rates. In crystallisation processes, the supersaturation can easily be controlled by thermal methods of evaporation or cooling. However, in precipitation, the creation of supersaturation is by a reaction, which commonly leads to high supersaturation. Thus, to obtain a product that has good filterability and settling ability, methods for controlling the supersaturation in precipitation reactions needs to be investigated.